Relocating the Literary: In Networks, Knowledge Bases, Global Systems, Material, and Mental Environments. Issue 1 (April 2017) - Tabbi, Joseph
Abstract : The cosmopolitan ideal of a world literature, only partially and occasionally realised in print, can give us terms with which to measure the costs and benefits of moving scholarly works, and our conversations about works, into present media. This essay takes a measuredly optimistic view of our current potential, as literature moves not simply from print to screen, across national borders, or among avant-garde aesthetics. The defining move, I want to argue, is from bounded forms to the database, whose works, while stable, remain open to linkages with all other literary forms available in any number of interoperable databases. The relocation of works in new media is a shift not in degree, but in kind. As our expectations too shift regarding the means of circulation among minds and media, we are more likely to discern what is really new and really global about writing in the media ecology and cognitive economies we currently inhabit.